Struggling for new narratives in slums and peripheries: complex citizenships amid material and cultural activisms - Comelli, Thaisa Cristina (Pontifícia Universidade Católica de São Paulo, 2021)
This article aims to discuss and explore new activisms in slums, focusing on the history, culture, and identity of such territories. We argue that, unlike the traditional urban activism commonly addressed in the literature (which focuses on demands of a material nature), the new activisms seek to add to such struggles a dispute over the narrative about the territory. We explore these manifestations in the light of debates about the conceptual transition of citizenship and intersectional identities. More specifically, we question the existence of a supposed slum-dweller identity in which hegemonic discourses and narratives about the city can be reproduced or subverted and used in the construction of insurgent urban struggles and activisms.